The UK’s role in normative fixing of common foreign policy of the European Union in Lisbon Treaty - Hrubinko, Andrii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article presents results of research participation of the UK in reforming the CFSP of the EU on the stage of development and adoption Lisbon Treaty (2006-2009). Position of governments of T. Blair and G. Brown regarding development of the CFSP is analyzed. Main novelties of the Treaty, formation of which is directly influenced by the country’s leadership are shown. The author came to the conclusion that in this period the Britain authorities departed from the strategy of leadership in Europe. The Treaty was consistent with a moderate British strategy of European integration. At the same time, the conclusion of the contract, who has made the most significant changes in CFSP, became a formal cause and a starting point for further revision of the relations Britain with the EU, which led to the beginning process of countries exit from the Union.